Stenting of the arterial duct in newborns with duct-dependent pulmonary circulation. Issue 7 (30th July 2007) - Santoro, G; Gaio, G; Palladino, M T; Iacono, C; Carrozza, M; Esposito, R; Russo, M G; Caianiello, G; Calabrò, R
Abstract : Objective: To evaluate the feasibility and results of stenting of the arterial duct in newborns with duct-dependent pulmonary circulation using low-profile, high-flexibility premounted coronary stents. Design: Prospective interventional and clinical follow-up study. Setting: Tertiary referral centre. Patient population: Between April 2003 and December 2006, 26 neonates (mean (SD) age 15.2 (19.9) days, mean (SD) weight 3.3 (0.8) kg) underwent attempts at stenting of the arterial duct. Main outcome measures: Procedural success and complication rates. Early and mid-term follow-up results. Results: The procedure was successfully completed in 24/26 (92.3%) cases. Minor complications occurred in 2/26 (7.7%) cases. No mortality occurred. After stenting, the ductal diameter increased from 1.2 (1.0) mm to 3.1 (0.4) mm (p<0.001) and the percutaneous O2 saturation increased from 70 (14)% to 86 (10)% (p<0.001), respectively. Over a mid-term follow-up, 2/24 patients (8.3%) needed a systemic-to-pulmonary artery shunt because of inadequate ductal flow and 4/24 patients (16.7%) underwent stent redilatation after 6.0 (4.4) months, but before corrective surgery. Cardiac catheterisation before corrective surgery in 9 patients showed an increase of the Nakata index from 112 (49) mm/mm 2 to 226 (108) mm/mm 2 (p<0.001), without any left-to-right imbalance of the pulmonary artery size. In the subset of 11 patients who improved without needing an additional source of pulmonary blood supply, the stented arterial duct closed uneventfully in 45.5% of cases after 4.0 (2.2) months. Conclusions: Stenting of the arterial duct is a feasible, safe and effective palliation in newborns with duct-dependent pulmonary circulation, supporting the spontaneous improvement process or promoting significant and balanced pulmonary artery growth for subsequent corrective surgery.